Pendampingan dan Peningkatan Perilaku Keagamaan Remaja Pasca Pendidikan Dasar melalui Kultur Pesantren di Desa Sindangbarang - Mukhlisin, Mukhlisin; Sofy, Malik (PELITA NUSA TENGGARA, 2025)
Adolescence marks a critical transition from childhood to adulthood, a period characterized by identity exploration and the pursuit of new experiences to build personal understanding. However, it is also a vulnerable stage, with many adolescents becoming involved in cases such as sexual harassment, gang violence, and bullying. Institutionally, religious education typically ends at the elementary level, where children attend MDTA (Madrasah Diniyah Takmiliyah Awaliyah) to establish basic religious foundations. After MDTA, there is no formal continuation structured by the government, leaving adolescents without sufficient guidance during this crucial phase. This community service program aims to instill the cultural values of the pesantren (Islamic boarding school), implement its practices, and evaluate its impact on strengthening religious behavior among teenagers. The mentoring activities successfully empowered adolescents to study classical Islamic texts (kitab kuning), recite the Qur'an and Hadith, enhance their worship practices, develop integrity-driven character, and maintain strong social ties. Parental, community, and government support further reinforced the program's success, introducing a new concept built on four pillars: spiritual, emotional, intellectual, and physical well-being. Through this holistic pesantren-based approach, adolescents achieved a balanced development that prepares them for future challenges.